Pelaksanaan Pendidikan Agama Islam Dalam Keluarga: Studi Kasus di Desa Alassumur Kecamatan Pujer, Kabupaten Bondowoso: The Implementation of Islamic Religious Education in the Family: A Case Study in Alassumur Village, Pujer Subdistrict, Bondowoso Regency - Sarwan Sarwan (Fenomena, 2003)
The implementation of Islamic religious education within the family is increasingly urgent amid concerns about moral divergence and the erosion of religious values in contemporary society. Islamic education is theoretically the foundation for shaping complete human beings (insan kamil) through lifelong learning. This study aims to describe how Islamic religious education is implemented and the roles parents play in carrying it out within families in Alassumur Village. A qualitative descriptive case study design was employed, using participant observation, unstructured interviews, and documentary methods to collect data from key informants, including village officials, religious leaders, community leaders, and residents. The findings reveal that Islamic religious education in the village encompasses three main areas: aqidah (faith), syari'ah (worship practices, including prayer, fasting, and zakat), and akhlak (morals toward God, parents, others, and the environment). Parents perform three primary roles: as instructors providing religious knowledge, as trainers modeling and practicing religious activities, and as counselors guiding and supervising children's behavior. The study concludes that family-based Islamic education is foundational for children's character development, and it recommends that parents increase time for direct guidance despite constraints such as work obligations. Pelaksanaan pendidikan agama Islam dalam keluarga semakin mendesak di tengah kekhawatiran terjadinya penyimpangan moral dan lunturnya nilai-nilai keagamaan dalam masyarakat kontemporer. Secara teoretis, pendidikan Islam berfungsi sebagai fondasi pembentukan manusia utuh (insan kamil) melalui proses pendidikan seumur hidup. Penelitian ini bertujuan mendeskripsikan pelaksanaan pendidikan agama Islam serta peran orang tua dalam keluarga di Desa Alassumur. Pendekatan kualitatif deskriptif dengan rancangan studi kasus digunakan, dengan metode observasi partisipan, wawancara tidak terstruktur, dan dokumentasi kepada informan kunci seperti perangkat desa, tokoh agama, tokoh masyarakat, dan warga. Temuan menunjukkan bahwa pendidikan agama Islam di desa tersebut mencakup tiga bidang utama: akidah, syariah (sholat, puasa, zakat), dan akhlak (kepada Tuhan, orang tua, sesama, dan lingkungan). Orang tua menjalankan tiga peran utama: sebagai pengajar yang memberikan pengetahuan agama, sebagai pelatih yang membiasakan praktik ibadah, dan sebagai pembimbing yang mengawasi perilaku anak. Kesimpulannya, pendidikan agama dalam keluarga merupakan fondasi utama pembentukan kepribadian anak, dan direkomendasikan agar orang tua meningkatkan waktu bimbingan langsung meskipun terdapat kendala seperti kesibukan kerja.